What Fundamentally Drives Growth? Revisiting the Institutions and Economic Performance Debate - Decker, Jessica Henson; Lim, Jamus Jerome (2012)
The recent empirical growth literature has proposed three underlying fundamental determinants of economic growth, namely, physical geography, economic integration and institutional quality. This paper unpacks the final determinant into both political-economic institutions as well as the primarily political institution of democratic development. Using both cross-sectional and panel datasets, we show that, properly instrumented, there is no evidence that democracies grow faster or slower than non-democracies. This result is in contrast to much of the more recent literature, which tends to find a weakly positive relationship. Political- economic institutions, however, remain positive and significant determinants of economic growth, which corroborates much of the empirical evidence in the existing literature.